Electrical and Electromechanical Converters: Lecture Notations - Zagradišnik, Ivan; Ritonja, Jožef (University of Maribor Press, 2025)
The publication is divided into five chapters: Introduction: magnetic field, excitation of windings, induction of voltage, forces and torque, conversion of electrical power into electrical or mechanical power, losses, efficiency, heating and cooling. Transformer: construction elements, ideal and real single-phase transformer, three-phase transformer, special transformer designs. Induction machine: description of construction with windings and mode of operation, starting motors and varying speed and torque, induction generator, single-phase induction motors. Synchronous machine: description of construction and operation, operation on a rigid grid, approximate treatment of a saturated machine, excitation systems and the use of permanent magnets for excitation, and permanent magnet synchronous motors.